Examining public acceptance of autonomous mobility - Caulfield, Brian (My University, 2020)
Over the last decade, the technology adopted for the automation of transportation has advanced at a pace that now the emergence of Autonomous Vehicles (AV’s) might not be as far away as it was thought a few years ago. However, the successful penetration of these vehicles in public roads will mainly rest upon their acceptance and adoption by individual road users and how they embrace this new generation of cars. This paper reports the results of a national survey study conducted among 475 Irish people to evaluate their interest in, and concerns about the adoption of AVs in their daily commute trends. The paper has also analysed people’s acceptance and Willingness to Pay (WTP) for AVs compared to Manually Driven Vehicles (MDVs). The results showed that people, in general, were not interested in driving AVs; only one-fifth of the population expressed a high level of interest. Concerns about recording data had an extreme and negative impact on interest since the majority of respondents were not ready to accept AVs' recording of data because of their concerns about privacy. People were also mostly unsure about or not likely to believe in the safety and security of AVs’ operation, and they were not at all willing to accept liability for AVs. In addition, the results revealed that cost substantially impacts people’s AV purchasing decisions, as when the cost was not an issue, people were much more interested in purchasing an AV.
PUBLISHED
Keywords: Autonomous Vehicles (AV); Willingness to Pay (WTP); Consumer behaviour; Smart & Sustainable Planet; autonomous vehicles; Attitudes; Transport